Case Report: Using Telehealth to Treat Triceps Tendinopathy in a Rock Climber - Vagy, Jared (Frontiers in Sports and Active Living, 2022)
This case study presents a 38-year-old, female rock climber with posterior elbow pain who was evaluated and treated using Telehealth. The use of telehealth for a clinical exam requires a larger emphasis be placed on posture observation and movement analysis since hands on assessment techniques cannot be used. During the patient exam, movement analyses identified scapulohumeral positional faults and dyskinesis, while self-palpation and self-midline resistance testing helped identify that the triceps tendon was the pathological tissue. A comprehensive rehabilitation program was developed based on concepts of regional interdependence to treat contributing factors in the scapular region and source tissues in the brachial region. After 10 weeks, the climber's pain decreased from 4/10 to 0/10. She made a full recovery back to her previous grade of V8 bouldering and was able to complete a V10 longstanding boulder project pain-free. This is the first case study of its kind to identify unilateral scapular dyskinesia in a patient with suspected triceps tendinopathy and to demonstrate a positive treatment effect by combining scapular strength exercises with eccentric exercises addressing the affected tissue.